Convergence Analysis of Economic Growth in South Kalimantan Province 2011-2019 - Yasari, Wira (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This study aims to analyze the convergence of economic growth in South Kalimantan Province in 2011-2019 based on the level of income per capita. The population of this research is the districts in South Kalimantan Province. Subjects take in the form of levels of income per capita with secondary data sourced from BPS. The analytical tools used are economic growth, Theil index, Williamson index, and Klassen typology model. This study also analyzes the relationship between economic growth and income inequality using Pearson correlation analysis. The results of this study indicate that there is a convergence of inequality in South Kalimantan Province in 2011-2019 with an average Williamson Index value at 0.496 and Theil index at 17.928. Based on the Klassen typology classification, only Tapin District is in the category of high developed and fast growing region. The output on the Pearson analysis correlation shows that there is a non-significant positive correlation between economic growth and income inequality. Furthermore, South Kalimantan Province does not support on the Kuznets hypothesis for the period 2011-2019.